2019
DOI: 10.5380/avs.v24i1.62475
|View full text |Cite
|
Sign up to set email alerts
|

Morfometria Intestinal E Qualidade Óssea De Codornas Japonesas Alimentadas Por Um Período Prolongado Com Coprodutos Do Óleo De Soja

Abstract: O objetivo do presente estudo foi avaliar os efeitos do uso prolongado de lecitina e óleo ácido de soja sobre a histologia duodenal e qualidade óssea de codornas japonesas na fase de postura. Foram utilizados 192 aves com 54 dias de idade as quais foram alimentadas durante 168 dias (metade da sua vida produtiva) com dietas contendo óleo degomado de soja (ODS) ou óleo acido de soja (OAS) associadas ou não com lecitina bruta de soja (LEC), totalizando 8 tratamentos descritos à seguir: T1 - dieta com 4% OAS; T2 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This represents a greater development of these structures and consequently a greater surface area for absorbing and harnessing energy from the litter (Santin et al, 2001;Baurhoo et al, 2007;Cunningham et al, 2004). Bavaresco et al (2019) observed that the inclusion of 1% lecithin in the diet did not affect the height of the villi. These results are similar to those of the present research, in which the use of emulsifier did not change intestinal histology, while there were significant effects when using different lipid sources.…”
Section: Discussionmentioning
confidence: 89%
“…This represents a greater development of these structures and consequently a greater surface area for absorbing and harnessing energy from the litter (Santin et al, 2001;Baurhoo et al, 2007;Cunningham et al, 2004). Bavaresco et al (2019) observed that the inclusion of 1% lecithin in the diet did not affect the height of the villi. These results are similar to those of the present research, in which the use of emulsifier did not change intestinal histology, while there were significant effects when using different lipid sources.…”
Section: Discussionmentioning
confidence: 89%
“…Os lipídios utilizados na dieta das aves possuem características químicas distintas, que exercem influência na sua digestibilidade pelo organismo, devido ao comprimento da cadeia carbônica, número de duplas ligações, configuração das duplas ligações (cis ou trans), posição do ácido graxo na molécula de glicerol e a relação de ácidos graxos insaturados e saturados (Nelson & Cox et al, 2014;Bavaresco et al, 2019).…”
Section: Introductionunclassified

Óleo de linhaça e óleo de coco na alimentação de frangos de corte

Lara Bordin Fernandes,
Batista Vieira Silva Gouveia,
Custódio Lamounier de Assis
et al. 2023
ISJM
“…According to [1,2], among the nutrients necessary for bird development, lipids stand out as sources of fatty acids that act in various metabolic functions of the organism. Nutrient adequacy, such as fatty acids for birds, can occur traditionally through the diet provided and be formulated according to recommendations for each animal phase by adding lipid sources rich in fatty acids derived from vegetable oils or animal fat [3].…”
Section: Introductionmentioning
confidence: 99%